(The most important cultural transformations in the Emirate of Ras Al Khaimah during the period 1982-2003) (Journal of the College of Basic Education, 2025)
Between the years 1982-2003, the Emirate of Ras Al Khaimah witnessed cultural transformations through the construction of many cultural institutions, heritage centers, and popular associations that contributed to improving the culture of the Emirati individual and helping him preserve his heritage, which is among the goals of the comprehensive development process followed in the Emirate of Ras Al Khaimah. Cultural development took several axes, the most important of which was the establishment of cultural centers and folk and heritage arts associations, The concerned authorities in popular institutions and associations were keen to demonstrate the emirate’s heritage values, reviving ancestral sports and hobbies such as camel racing, rowing, and handicrafts, and holding exhibitions that support communication between generations, and deepening societal customs and traditions in the souls and behavior of the population.The Ras Al Khaimah government has also worked to develop the literary and theatrical movement by establishing sports and cultural clubs, in addition to encouraging tourism by developing the tourism sector and promoting its institutions. Tourism has become an economic, recreational and cultural source, by spreading awareness of the importance of heritage and its sustainability and transferring it to new generations through organizing seminars, conferences, events and workshops. The Emirate of Ras Al Khaimah has emerged among the rest of the Emirates of the country with its unique cultural character that combines authenticity and innovation.